Identification and Stenting of Malignant Obstructive Jaundice : Determining the Success Rates of ERCP - Budi Tan Oto; Achmad Fauzi; Ari Fahrial Syam; Marcellus Simadibrata; Murdani Abdullah; Dadang Makmun; Chudahman Manan; Abdul Aziz Rani; Daldiyono Daldiyono (The Indonesian Journal of Gastroenterology, Hepatology, and Digestive Endoscopy, 2012)
Background: Malignant and benign lesions may cause obstructive jaundice. The treatment of these conditions includes biliary stenting drainage, percutaneous transhepatic biliary drainage (PTBD), or surgical procedures. In advanced malignant jaundice, stent placement often turns out to be difficult. The aim of this study was to determine the success rates of malignant obstructive jaundice detection utilising endoscopic retrograde cholangiopancreatography (ERCP) and its stent placement procedure. Method: We conducted a retrospective study in 139 patients who undergone ERCP in Cipto Mangunkusumo Hospital between October 2004 and July 2008. Data was analyzed descriptively with SPSS version 17.0. Results: Of 139 study subjects, 131 (94.2%) of them had clinical obstructive jaundice (direct bilirubin indirect bilirubin level). There were 73 (55.7) male patients, with age range of 20-84 years. Among 114 patients with identified cause of obstruction, 57 (50%) patients had undergone stent placement; however, only 32 (56.1%) patients had successful stent placement. Our descriptive analysis showed that age and sex did not affect the stent success rates, and malignancy was showed to be a factor of stent failure. Conclusion: ERCP appears to be reliable enough for identifying the cause of obstructive jaundice in most patients. In this study, the achieved success rate of stent placement is more than 50%. Moreover, such rate is lower in the malignant obstructive jaundice than the non-malignant counterparts. Papillary carcinoma is the most frequent cause of malignant obstructive jaundice. Keywords: ERCP, obstructive jaundice, stenting, malignancy